Pharmacological senolysis reduces doxorubicin-induced cardiotoxicity and improves cardiac function in mice - Araceli Lérida-Viso; Alejandra Estepa- Fernández; Ángela Morellá-Aucejo; Beatriz Lozano-Torres; María Alfonso; Juan F. Blandez; Viviana Bisbal; Pilar Sepúlveda; Alba García-Fernández; Mar Orzáez; Ramón Martínez-Máñez (Elsevier, 2022)
Many anticancer agents used in clinics induce premature senescence in healthy tissues generating accelerated aging processes and adverse side-effects in patients. Cardiotoxicity is a well-known limiting factor of anticancer treatment with doxorubicin (DOX), a very effective anthracycline widely used as antitumoral therapy in clinical practice, that leads to long-term morbidity and mortality. DOX exposure severely affects the population of cardiac cells in both mice and human hearts by inducing premature senescence, which may represent the molecular basis of DOX-induced cardiomyopathy. Here, we demonstrate that senescence induction in the heart contributes to impaired cardiac function in mice upon DOX treatment. Concomitant elimination of senescent cells with the senolytic Navitoclax in different formulations produces a significant decrease in senescence and cardiotoxicity markers together with the restoration of the cardiac function in mice followed by echocardiography. These results evidence the potential clinical use of senolytic therapies to alleviate cardiotoxicities induced in chemotherapy-treated patients.